2007
DOI: 10.1261/rna.577707
|View full text |Cite
|
Sign up to set email alerts
|

Specific trans-acting proteins interact with auxiliary RNA polyadenylation elements in the COX-2 3′-UTR

Abstract: Two cyclooxygenase (COX) enzymes, COX-1 and COX-2, are present in human cells. While COX-1 is constitutively expressed, COX-2 is inducible and up-regulated in response to many signals. Since increased transcriptional activity accounts for only part of COX-2 up-regulation, we chose to explore other RNA processing mechanisms in the regulation of this gene. Previously, we showed that COX-2 is regulated by alternative polyadenylation, and that the COX-2 proximal polyadenylation signal contains auxiliary upstream s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 67 publications
3
91
0
Order By: Relevance
“…We find that U1A binds directly to sequences flanking the polyadenylation site in the 3Ј-UTR of the SMN pre-mRNA. In addition to being a component of the U1 snRNP, U1A is also known to bind to several mRNAs and regulates their polyadenylation (35,47,48). We show here that binding of U1A inhibits polyadenylation of the SMN pre-mRNA by specifically blocking 3Ј cleavage of the transcript by the CPSF73 endonuclease.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We find that U1A binds directly to sequences flanking the polyadenylation site in the 3Ј-UTR of the SMN pre-mRNA. In addition to being a component of the U1 snRNP, U1A is also known to bind to several mRNAs and regulates their polyadenylation (35,47,48). We show here that binding of U1A inhibits polyadenylation of the SMN pre-mRNA by specifically blocking 3Ј cleavage of the transcript by the CPSF73 endonuclease.…”
mentioning
confidence: 75%
“…Interestingly, we also identified SNRPA (U1A), a bifunctional protein primarily involved in pre-mRNA splicing but also shown to function in regulated polyadenylation. We additionally identified NONO (p54 nrb ), SFPQ (PSF), and PTBP1 (PTB), three factors known to bind snRNP-free U1A and function with it in polyadenylation (48,52,53). In addition to factors involved in polyadenylation, we identified Gemin5, the RNA-binding protein of the SMN complex (54).…”
Section: Identification Of Proteins That Bind the Polyadenylation Sitmentioning
confidence: 99%
“…We have previously shown that U1A, PTB, PSF and p54 proteins bind to upstream polyadenylation efficiency elements present in the COX-2 polyadenylation signal 32 and others have demonstrated that a similar complex of proteins binds to similar elements in the prothrombin 3'UTR. 33 These protein factors are especially note-worthy since they are also mRNA splicing factors, suggesting the functional coupling of splicing and 3'end formation.…”
Section: Discussionmentioning
confidence: 96%
“…Additional cis-acting elements that function to alter the efficiency of polyadenylation have also been identified as auxiliary RNA elements. 117,118 However, once the signal is recognized by the cleavage/ polyadenylation complex in the nucleus, the full-length poly(A) tail is added to the cleaved 3' end. No regulatory mechanisms have been described yet at this first round of polyadenylation, suggesting that addition of a poly(A) tail is a default modification after mRNA 3' cleavage in the nucleus.…”
Section: Cis-elements Involved In Polyadenylation/deadenylationmentioning
confidence: 99%